The macroeconomics of East Asian growth - Wu, Yanrui (E. Elgar Pub., 2002)
"Yanrui Wu addresses some of the most critical macroeconomic issues associated with East Asian growth. Principally focusing on the most rapidly emerging economies in the region, the author covers a broad base of topics. Several determinants of growth are examined and in each case an analytical framework is applied to empirical data." "Employing both cross-country analyses and case studies of individual economies, this book contributes to the many debates surrounding economic growth in East Asia. The author's style will appeal to economic researchers, lecturers and students of economics, as well as business economists and market analysts."--BOOK JACKET.